2018
DOI: 10.1113/jp275681
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific activation of SK current by isoproterenol facilitates action potential triangulation and arrhythmogenesis in rabbit ventricles

Abstract: Sex has a large influence on cardiac electrophysiological properties. Whether sex differences exist in apamin-sensitive small conductance Ca -activated K (SK) current (I ) remains unknown. We performed optical mapping, transmembrane potential, patch clamp, western blot and immunostaining in 62 normal rabbit ventricles, including 32 females and 30 males. I blockade by apamin only minimally prolonged action potential (AP) duration (APD) in the basal condition for both sexes, but significantly prolonged APD in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…As SK channels appears to play a role in some pathological conditions in the ventricles (Gui ; Bonilla ; Hundahl ; Chen ; Hamilton ), it could be speculated that the SK channels also have a contributory role in the pathogenesis of CaM‐associated LQTS. Three out of the four LQTS‐associated CaM variants significantly down‐regulated the SK current, with CaM D130G being the variant most profoundly decreasing SK current with no effect on the trafficking of the channel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As SK channels appears to play a role in some pathological conditions in the ventricles (Gui ; Bonilla ; Hundahl ; Chen ; Hamilton ), it could be speculated that the SK channels also have a contributory role in the pathogenesis of CaM‐associated LQTS. Three out of the four LQTS‐associated CaM variants significantly down‐regulated the SK current, with CaM D130G being the variant most profoundly decreasing SK current with no effect on the trafficking of the channel.…”
Section: Discussionmentioning
confidence: 99%
“…This atrial selectivity makes SK channels an interesting target in the treatment of atrial arrhythmias, as the ventricular side effects have been speculated to be avoided (Xu ; Diness , ; Skibsbye ; Skibsbye ). However, several recent studies have shown that SK channel current also becomes functional in the ventricles during enhanced sympathetic activation through β ‐adrenergic stimulation (Chen ; Hamilton ).…”
Section: Introductionmentioning
confidence: 99%
“…Expressions of SK2 channel and SK current density are higher in ventricular myocytes of female rabbits compared to male rabbits [ 14 ]. Furthermore, action potential triangulation, a known proarrhythmic predictor, is observed in female rabbit hearts upon isoproterenol stimulation, which could be reversed by apamin, suggesting the possible roles of SK channels in ventricular fibrillation in female animals during sympathetic stimulation.…”
Section: Regulation Of Cardiac Sk Channelsmentioning
confidence: 99%
“…The study by Chen et al . () provides clear evidence that SK channels are important contributors to the shape of the ventricular AP under conditions simulating increased sympathetic drive, and that SK channel inhibition might be a promising antiarrhythmic strategy for pharmacological treatment of ventricular fibrillation, particularly in females. Although block of SK channels may prolong ventricular AP, preventing reentrant arrhythmias, it may make the ventricular cardiomyocytes more sensitive to Ca 2+ ‐dependent triggered activity (Hsueh et al .…”
mentioning
confidence: 95%
“…As reported in this issue of The Journal of Physiology , Chen et al . () studied sex‐specific SK channel activation in the ventricle, particularly in settings mimicking increased sympathetic drive, which accompanies many pathophysiological conditions and the physiological ‘fight‐or‐flight’ response. In ventricular cardiomyocytes from both male and female rabbits, the highly selective SK channel blocker apamin caused only a small prolongation of the AP under basal conditions.…”
mentioning
confidence: 99%